ANALYSIS OF VILLAGE DEVELOPMENT IN PESISIR BARAT REGENCY USING THE SCALOGRAM APPROACH, CENTRALIZATION INDEX, AND TOPSIS METHOD - Royiv Agmadeni; I Wayan Suparta; Arivina Ratih Yulihar Taher (ZILLZELL MEDIA PRIMA, 2025)
Village development plays a crucial role in driving regional economic growth. The implementation of the Village Law has accelerated development in rural areas, though inequality remains a major challenge. One way to address this issue is by identifying growth center villages through comprehensive analysis. This study uses a descriptive-analytical approach covering 116 villages in Pesisir Barat Regency. The objective is to identify villages that act as growth centers and hinterlands, helping to highlight areas with high development intensity. Three methods are used: scalogram analysis, centralization index, and the TOPSIS method. Scalogram analysis identified 6 growth center villages and 6 hinterland villages. The centralization index revealed 4 service center villages and 3 hinterland villages, with most villages classified as very underdeveloped in terms of facilities. Using the TOPSIS method, the study found that only 7% of villages had high development intensity, while the majority had moderate levels. These findings emphasize the need for a more balanced distribution and improvement of village facilities, particularly those that can stimulate broader economic impacts.